Aplikasi Kompos Dengan Aktivator Effective Microorganisms 4 (EM 4) Dan Pupuk Organik Cair NASA Pada Pertumbuhan Bibit Batang Bawah Tanaman Karet (Hevea brasiliensis) - Wandi Fahrin; Mahdalena Mahdalena; Hamidah Hamidah (Universitas Widya Gama Mahakam, 2017)
Application of Compost With Effective Microorganisms Activator 4 (EM 4) And NASA Fluid Organic Fertilizer At Growth Of Rubber Trunk Bottom Plant (Hevea brasiliensis). This study aims to determine the effect of application of compost fertilizer with activator Effective Microorganisms 4 (EM 4) and the effect of Nasa liquid organic fertilizer application on the growth of rootstock seedling of rubber plant. The study was conducted for 3 months starting from May 5 to August 5, 2015 Loa Janan Ulu Village Kutai Kertanegara Regency. The study used Randomized Block Design (RAK) with 4 x 4 factorial experiment with 3 replications. The first factor is the application of compost treatment consisting of 4 levels, namely: k0 Tanah (topsoil), k1 = Soil: Compost = 1: 1, k2 = Soil: Compost = 1: 2, k3 = Soil: Compost = 1: 3. While the second factor is the application of liquid organic fertilizer NASA consisting of 4 levels, namely: p0 = Control, p1 = 2 ml / L water, p2 = 4 ml / L water, p3 = 6 ml / L water. The result of variance indicated that application of compost fertilizer had a very significant effect on the height of 3 month crop, the increase of stem diameter month 2, month 3, the increase of monthly leaf number 2, month 3. Furthermore significant effect on the increase of plant height month 1, month 2, Stem diameter month 1, and month leaf number increase 1. Application of NASA (P) liquid organic fertilizer had a very significant effect on the parameters of plant height increase in month 2, month, 3, month stem diameter 2, month 3, Month 3. Then the real effect on parameters of plant height month month 1, and the increase of number of leaves month 1. For interaction application of Compost Fertilizer and organic fertilizer Nasa (KxP) no significant effect on parameters of plant height increase month 1, month 2, month 3, the increase of number of leaves month 1, month 2, month 3, the increase of stem diameter month 1, month 2 and month 3. Keywords: Effective Microorganisms 4, Liquid Fertilizer Nasa and Rubber Plants